Mobile concierge services. - Tan, Gui De. (2010)
This paper explores how to better enhance tourists’ mobile concierge services. Mobile concierge service refers to the delivery of services useful to tourists through mobile phones. It is suitable as a pre-purchase, external source of information search. Tourists who are likely to use mobile concierge service are frequent travellers, those with families, vacationers and those who perceive greater economic risk of bad purchase. Business travellers could use mobile concierge service as well. Given the nature of information access by tourists, the service provided must be fast, up to date, trustworthy and contextually aware. The proposed model incorporates both voice-based services as well as mobile application services.